Perceived learning and satisfaction in a blended teacher education programme : a survey of IIUM teacher trainees - Karimi, Leila (Institute of Education, International Islamic University Malaysia, 2013)
Blended learning, as a new approach to education, is rapidly being adopted by educational institutions for the purpose of teacher education or teacher training. This study reports the results of a survey exploring the relationships between perceived learning and satisfaction in a blended teacher education programme among three different groups of specialization including Teaching English as Second Language (TESL), Islamic Education (ISED), and Guidance and Counseling (GUIDE) at the Institute of Education, International Islamic University Malaysia (IIUM). The respondents consisted of 170 teacher trainees from the three specializations randomly selected through quota sampling. The instrument used to collect data was a modified questionnaire containing 23 items that measured the respondents' perception of learning and satisfaction in the blended teacher education programme. The internal consistency index for perceived learning was 0.77, while that of satisfaction was 0.88. The data were analyzed using descriptive statistics, correlational analysis using the Pearson Product-Moment Correlation Coefficient (Pearson's r), and One-way MANOVA. The teacher trainees reported high levels of perceived learning and satisfaction toward the IIUM blended teacher education programme as indicated by the descriptive analysis. The correlational analysis showed positive and moderate correlation between perceived learning and satisfaction, while the results of one-way MANOVA indicated that there was no statistically significant difference among TESL, ISED and GUIDE teacher trainees' perception of learning and satisfaction. The findings provide information for higher learning institutions in order to create better teacher education programmes. In addition, the findings also give insights that can support services which may lead to more effective blended learning environments. Since perceived learning and satisfaction are factors known to influence the success of blended learning programmes, the study made recommendations that the these two factors be looked into in greater depth in future research to find out what is needed to improve satisfaction and perceived learning in a blended teacher education programme.